2013
DOI: 10.1002/tesj.126
|View full text |Cite
|
Sign up to set email alerts
|

Focusing on Content: Discourse in L2 Peer Review Groups

Abstract: Recent studies on peer review groups in second language classes have focused on various topics, including collaboration (Carr, 2008) and the effect of peer review versus teacher feedback on students' writing (Zhang, 1995). One area that has received little attention is the content of students' speech during peer review. This longitudinal case study examined English as a second language (ESL) students' oral discourse during peer feedback sessions to explore the types of comments ESL students choose to make duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 40 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…Second, we emphasize that instructional interventions must rely on a well-designed feedback process. To ensure the quality of peer review, we applied a two-step (Vorobel & Kim, 2014) feedback design that began with L1 oral comments, followed by L2 written feedback. The first step in L1 led to a larger quantity of comments in which the native language helped maximize students' understanding (De Guerrero & Villamil, 2000;Kamimura, 2006;Zhao, 2010).…”
Section: Conclusion and Closing Commentsmentioning
confidence: 99%
“…Second, we emphasize that instructional interventions must rely on a well-designed feedback process. To ensure the quality of peer review, we applied a two-step (Vorobel & Kim, 2014) feedback design that began with L1 oral comments, followed by L2 written feedback. The first step in L1 led to a larger quantity of comments in which the native language helped maximize students' understanding (De Guerrero & Villamil, 2000;Kamimura, 2006;Zhao, 2010).…”
Section: Conclusion and Closing Commentsmentioning
confidence: 99%
“…Once again, for these studies focusing on CAPR, we identified the mode of peer feedback exchanges based on the technological tools used: synchronous, asynchronous, or a combination of synchronous and asynchronous CAPR. Out of the 37 reviewed studies, 15 previous studies focused on FFPR only (Stanley, 1992;Beason, 1993;Mendonca & Johnson, 1994;Lockhart & Ng, 1995;Zhu, 1995;Mendonca & Johnson, 1994;Villamil & De Guerrero, 1996;McGroarty & Zhu, 1997;De Guerrero & Villamil, 2000;Zhu, 2001;Min, 2005;Cho & Cho, 2011;Lina & Samuel, 2013;Vorobel & Kim, 2014;Hanjani & Li, 2014). On the other hand, an equal number of studies (N = 15) concentrated on CAPR only (Tuzi, 2004;Hewett, 2006;Guardado & Shi, 2007;Liang, 2008Liang, , 2010Liou & Peng, 2009;Ho & Usaha, 2009;Anderson, Bergman, Bradley, Gustafsson, & Matzke, 2010;Cha & Park, 2010;Ho, 2010;Ho & Usaha, 2013;Bradley, 2014;Razak & Saeed, 2014;Pham & Usaha, 2015;Saeed & Ghazali, 2016).…”
Section: Data Collectionmentioning
confidence: 99%
“…Regarding this, five studies identified the focus areas of revision-oriented feedback in FFPR as in Table 3. Four of these studies (Beason, 1993;Lockhart & Ng, 1995;Min, 2005;Vorobel & Kim, 2014) indicated that peer feedback focused on issues of writing at the macro-level, such as idea development, organization and purpose more than issues at the micro level, such as mechanics and grammar. On the other hand, Hanjani and Li (2014) reported that most of EFL learners' interactional exchanges focused on micro-level issues such as grammar, while a few comments focused on macro-level issues such as content and organization.…”
Section: The Focus Areas Of Interactional Feedback Exchanges In Peer mentioning
confidence: 99%
See 1 more Smart Citation
“…Pritchard and Morrow (2017) refer to social benefits of FFPR as students deal with non-threatening audience which has similar characteristics like them, they receive comments immediately in a direct way, the act of exchanging peer comments can be exciting because it reduces the writing apprehension, motivation for writing increases as students assume the process as something collaborative, and the interpersonal communication and sense of cooperation are developed. Some studies only examined the differential effects of FFPR (Cho & Cho, 2011;Hanjani & Li, 2014;Min, 2005;Vorobel & Kim, 2014), whereas some other studies have compared FFPR with computermediated peer review (CMPR) (Chang, 2012;Ho, 2015;Liu & Sadler, 2003;Rouhshad, Wigglesworth, & Storch, 2016;Yilmaz, 2012) and argued that the difference in the mode of interaction has affected the number, area, nature, and type of peer comments as well as students' revision skills and writing performance.…”
Section: Face-to-face Peer Review (Ffpr)mentioning
confidence: 99%